2012
DOI: 10.2169/internalmedicine.51.6262
|View full text |Cite
|
Sign up to set email alerts
|

Tophaceous Gout in the Cervical Spine

Abstract: A 58-year-old woman with a three-year progressive history of chronic arthritis, had become disabled due to general malaise and fever. Her laboratory data revealed hyperuricemia and elevated levels of C-reactive protein. Neither rheumatoid factor nor anti-citrullinated peptide antibodies were present. We diagnosed her with tophaceous gout with uric crystalline revealed by the arthrocentesis of the elbow. 99m Tc scintigraphy also disclosed a significant uptake in the cervical spine. The CT of the patient's cervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…WBC count, serum CRP level, and ESR are not specific in spinal gout, but elevated levels of serum uric acid are known to positively contribute to the development of spinal gout. [14,15] In our study, only 2 patients had leukocytosis and elevated serum CRP levels, whereas all of the patients had elevated serum uric acid levels and ESR. Therefore, the possibility of spinal gout should be considered when a patient presents with a history of gout or elevated uric acid level along with axial pain, radicular pain, or myelopathy.…”
Section: Discussionmentioning
confidence: 47%
“…WBC count, serum CRP level, and ESR are not specific in spinal gout, but elevated levels of serum uric acid are known to positively contribute to the development of spinal gout. [14,15] In our study, only 2 patients had leukocytosis and elevated serum CRP levels, whereas all of the patients had elevated serum uric acid levels and ESR. Therefore, the possibility of spinal gout should be considered when a patient presents with a history of gout or elevated uric acid level along with axial pain, radicular pain, or myelopathy.…”
Section: Discussionmentioning
confidence: 47%
“… 12 , 15 , 21 Other CT findings include degenerative changes, lytic lesions, and spinal stenosis. 22 – 25 We found that it was not easy to diagnose this disease radiographically. Are there any imaging methods with high specificity and accuracy to diagnose spinal tophaceous gout?…”
Section: Discussionmentioning
confidence: 97%
“…Preoperatively, pharmaceutical treatment was given to relieve pain, nourish nerve and dehydrate [1]. To immediately decompress the nerve root symptoms, surgical treatment including anterior cervical corpectomy, debridement and fusion, and internal fixation of C5–6 was performed [1, 8, 11]. After surgery, the muscle strengths of limbs were significantly improved.…”
Section: Case Presentationmentioning
confidence: 99%